2017
DOI: 10.5539/gjhs.v10n1p111
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Professional Commitment and Its Effect on Patient Safety

Abstract: Aims and objectives: The project was designed to assess the level of professional commitment among Jordanian Registered Nurses and examine how professional commitment among nurses relates to patients' safety. Background:Professional commitment has received a great deal of interest worldwide. Nurses constitute the largest group of healthcare professionals that spend a majority of their time at the bedside in direct patient care. Nurses have an important role in improving patient safety and providing quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 15 publications
3
23
0
2
Order By: Relevance
“…Furthermore, a study conducted in Estonia reported no relationship between workplace commitment and burnout amongst nurses [ 58 ]. As there are indications that workplace commitment is correlated with patient safety [ 59 ], the development and improving of workplace commitment needs further scientific investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study conducted in Estonia reported no relationship between workplace commitment and burnout amongst nurses [ 58 ]. As there are indications that workplace commitment is correlated with patient safety [ 59 ], the development and improving of workplace commitment needs further scientific investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In medicine and nursing, experts have raised awareness that professional values should be taught to starting professionals in order to create a shared culture of practice and stimulate a commitment to the profession's values . Such a commitment may improve patients’ health outcomes, as was found in a recent study among nurses …”
Section: Introductionmentioning
confidence: 72%
“…[12,18] Such a commitment may improve patients' health outcomes, as was found in a recent study among nurses. [19] Despite limited research, professional values of pharmacy practice appear, often implicitly, in pledges of professionalism. For example, in many countries, pharmacists take public oaths, mostly at the graduation ceremonies of pharmacy schools.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses' reluctance in using diapers is reflected in findings of the recent research, although some nurses are comfortable in using diaper because of being habituated to it. As nurses' professional commitment and its effect on patient care is not correlated with years of expertise (Al-Hamdam, Dalky, & Al-Ramadneh, 2018), novice nurses have better flexibility to adopt new idea/device than do experts. Although the developed pad might still look like a diaper, it is not a diaper.…”
Section: Discussionmentioning
confidence: 99%